2018
DOI: 10.1016/j.bioelechem.2018.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Electropermeabilization of cells by closely spaced paired nanosecond-range pulses

Abstract: Decreasing the time gap between two identical electric pulses is expected to render bioeffects similar to those of a single pulse of equivalent total duration. In this study, we show that it is not necessarily true, and that the effects vary for different permeabilization markers. We exposed individual CHO or NG108 cells to one 300-ns pulse (3.7-11.6 kV/cm), or a pair of such pulses (0.4-1000 μs interval), or to a single 600-ns pulse of the same amplitude. Electropermeabilization was evaluated (a) by the uptak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…16 These abnormalities were thought to be of potential concern for nsPEF use in defibrillation. The underlying mechanisms have not been explored yet and may involve permeabilization of the sarcoplasmic reticulum by nsPEF, [18][19][20] damage to voltage-gated Ca 2+ channels, 15 alteration of phosphoinositide signaling, [21][22][23] and nanoelectroporation of the cell membrane (which can be detected by the loss of membrane potential and transport of water and small ions, but not by propidium uptake). 11,12,19,[24][25][26] The present study was aimed at testing the latter mechanism by exploring if there are any abnormal responses upstream from Ca 2+ handling, namely at the level of the action potential (AP) induction by nsPEF.…”
mentioning
confidence: 99%
“…16 These abnormalities were thought to be of potential concern for nsPEF use in defibrillation. The underlying mechanisms have not been explored yet and may involve permeabilization of the sarcoplasmic reticulum by nsPEF, [18][19][20] damage to voltage-gated Ca 2+ channels, 15 alteration of phosphoinositide signaling, [21][22][23] and nanoelectroporation of the cell membrane (which can be detected by the loss of membrane potential and transport of water and small ions, but not by propidium uptake). 11,12,19,[24][25][26] The present study was aimed at testing the latter mechanism by exploring if there are any abnormal responses upstream from Ca 2+ handling, namely at the level of the action potential (AP) induction by nsPEF.…”
mentioning
confidence: 99%
“…The high PRF (1 MHz) of nanosecond pulses allowed to achieve significant increase of the transfected cells (up to 17% of cells being GFP positive), which was not possible in 1 Hz–10 kHz range. The phenomenon could be partly justified by the accumulation of charge on the cell membrane when the relaxation time is longer compared to the delay between the pulses, which results in the increase of transmemebrane voltage potential and thus increased permeabilization rate 43 , 49 , 50 . However, it does not explain the increased DNA electrotransfer rate, which requires electrophoresis that is limited during short pulses.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the response of cells (determined by propidium iodide permeabilization assay) to high PRF was several-fold higher if compared to low frequency protocols. Recently, similar result was confirmed by Semenov et al ., where authors of the study showed that the uptake of YO-PRO-1 is doubled when the nanosecond pulses are closely spaced 50 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the delivery of two identical pulses of the same polarity (paired pulses) separated by a certain time gap was investigated. Additive or supra-additive effects were obtained on YP or Tl + ions uptakes or Ca 2+ transients after exposure to single 600 ns or 300 ns paired pulses compared to a single 300 ns, with different interpulse interval from 0.4 to 1000 µs [12]. Likewise, two paired pulses with single duration of 300 ns separated by 50 μs caused two-fold greater membrane permeabilization than a comparable bipolar nsPEF treatment [4].…”
Section: Introductionmentioning
confidence: 91%